Multidisciplinary management on the integral treatment in dentistry. Case report - Cabello Chávez, Miguel (2015)
It is extremely important the multidisciplinary management of treatment in dentistry, to diagnose and establish an appropriate treatment plan for the patient benefit and satisfaction. The aim of this case was to achieve a proper functioning of the masticatory system while restoring the patient aesthetics, through a multidisciplinary dental management. A female patient 60, attended the School of Dentistry at Universidad Nacional Mayor de San Marcos because she had difficulty chewing her food. Clinical examination revealed diastema between the upper front teeth, crowns in disrepair and partial absence of teeth. Radiographically it was observed that the piece 48 has not erupted. Additionally has a tooth withheld. Extractions, metal ceramic restorations, removable partial dentures, multiple treatments were performed. In conclusion the multidisciplinary management in dentistry leads to favorable results providing broader treatment possibilities for patients approach.